OPTIMAL MATERIAL PARAMETERS CHOICE FOR COMPOSITE SHAFTS MANUFACTURING - Saša Jovanović; Zorica Đorđević; Sonja Kostić; Danijela Nikolić; Miloš Matejić (International Journal for Quality Research)
In past decades, various multi-criteria decision-making (MCDM) techniques have become effective tools for determining the optimal input parameters of various processes. An overview of the application of various MCDM techniques in solving the problem of parametric optimization of the processing process gives a concise picture and the possibility of easier selection of a certain method in the decision-making process. This paper shows the choice of optimal parameters for composite shaft manufacturing. The composite shaft has with ring cross-section, and it consists of aluminum as the base material with a coating of different fiber types covered with epoxy. For optimal parameter choice, different MCDM techniques are used. The most influential parameters are determined. The paper concludes with discussion of the used parameters with guidelines for optimal parameter choice for composite shaft manufacturing.